Unveiling the Factors Behind the Shadow Economy: A Global Investigation Utilizing Panel Data Analysis - Mihai-Adrian Achim; Codruța Mare (Revista de Studii Financiare, 2024)
The paper addresses the topic of the shadow economy and the socio-economic factors that influence it. By reviewing relevant studies, we will observe that a variety of factors play a role in shaping this economy. Using a dataset comprising 50 countries from around the world, monitored over 13 years, we conducted an analysis to determine which of the discussed factors most significantly impact the level of the shadow economy. The OLS model shows a positive relationship between income inequality, the unemployment rate and the shadow economy and a negative relationship between the World Governance Index, income inequality and the shadow economy. We will find that this model will have autocorrelation problems that might influence the significance of the coefficients. Our main model (the GMM one) addresses autocorrelation and heteroskedasticity but shows some different outcomes. The findings can serve as a valuable resource for other researchers or even governments, helping to identify what changes are needed to reduce the share of the shadow economy. By the end of this research, we will have identified the key areas that need enhancement and growth to effectively address and reduce the shadow economy.